HUBUNGAN PENGETAHUAN IBU TENTANG TOILET TRAINING DENGAN KEJADIAN ENURESIS ANAK USIA PRESCHOOL (4-5 TAHUN) (Studi Analitik di TK Al-Mutaqin Desa Besuk Kecamatan Gurah Kabupaten Kediri 2014) - Kosasih, Ikhwan; Utomo, Andri Fuji (Jurnal AKP, 2014)
Toilet training is practice to urinate and defecate in toilet that taught at child at age 4 â 5 years so it can overcome enureses that caused by ability of organ finction that arrange feel wish urinate and defecate has started to expand but still in rough. Reseach design classified as non experimental with approach of cross sectional. In this resach use 2 variables. Independent variable is mother knowledge about toilet training with questionnaire instrumen. Dependent variable is incident of child enuresis at age 4 â 5 years with questionnaire instrumen.Â  The total population is 30 mothers. With Total sampling. So this total sample is 30 mothers. Then analyzed using Chi square.Base to result of research for knowledge, it is obtained good 26,7%, enough 23,3%, and bad 50%. Whereas for the dependent variables that are not enuresis 36,7% and enuresis 63,3%. To know correlation between the independent variable and dependent variable used SPSS documen processing for window with the formula chi square. It is obtained (r) = 0,000 with a = 0,05. Â Thus r < a so H0 are refused andÂ  H1 are accepted. From the final result of correlation of Chi Square price value = 0,656 with (P) = 0,000 with level of mistake 5%.. With P < a then H0 are refused and H1 are accepted. This condition indicates that there is relation between mother knowledge about toilet training with incident of child enuresis at age 4 â 5 years. Because the motherâs knowledge are good aboutÂ  toilet training to effect on incidence of enuresis. If the mother have understand about toilet training then it would apply to their children.Â Keywords : knowledge, mother, toilet training, enuresis, preschools